2022
DOI: 10.3390/plants11162088
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Analysis of the Aureochrome Gene Family in Saccharina japonica and a Comparative Analysis with Six Other Algae

Abstract: Aureochrome (AUREO) is a kind of blue light photoreceptor with both LOV and bZIP structural domains, identified only in Stramenopiles. It functions as a transcription factor that responds to blue light, playing diverse roles in the growth, development, and reproduction of Stramenopiles. Most of its functions are currently unknown, especially in the economically important alga S. japonica farmed on a large scale. This study provided a comprehensive analysis of the characteristics of AUREO gene families in seven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…In the case of diatoms, P. tricornutum is a versatile study subject, yet not representative for the dominant diatom species found in the world oceans. Recent studies on Nannochloropsis oceanica ( Poliner et al , 2022 ) and the brown seaweed Saccharina japonica (sweet kelp) ( Wu et al , 2022 ) are starting to address this, but major stramenopile lineages with diverse lifestyles have yet to be investigated. The recent expansions in molecular tools and sequencing resources for ecologically important stramenopile species will allow us to compare the light regulatory machineries of diatoms and other stramenopiles evolved in a diversity of light fields, such as the polar diatom Fragilariopsis cylindrus that is subjected to prolonged periods of darkness.…”
Section: Going Forwardmentioning
confidence: 99%
“…In the case of diatoms, P. tricornutum is a versatile study subject, yet not representative for the dominant diatom species found in the world oceans. Recent studies on Nannochloropsis oceanica ( Poliner et al , 2022 ) and the brown seaweed Saccharina japonica (sweet kelp) ( Wu et al , 2022 ) are starting to address this, but major stramenopile lineages with diverse lifestyles have yet to be investigated. The recent expansions in molecular tools and sequencing resources for ecologically important stramenopile species will allow us to compare the light regulatory machineries of diatoms and other stramenopiles evolved in a diversity of light fields, such as the polar diatom Fragilariopsis cylindrus that is subjected to prolonged periods of darkness.…”
Section: Going Forwardmentioning
confidence: 99%
“…Analysis of gene families was mainly carried out with reference to an earlier paper (Wu et al, 2022). All network addresses needed for online analysis are summarized in Supplement Table . 3.…”
Section: Phylogenetic and Structural Analysis Of Cpfmentioning
confidence: 99%
“…The differential expression changes of Sj CPFs in different developmental stages of S. japonica gametophyte were derived from transcriptome data (PRJNA816677) reported by Wu et al (2022). Transcriptome data are divided into four distinct stages according to different time points during gametophyte development: Dormant period (0 d), Vegetative growth period (3 d), Vegetative growth peak (6 d), and Gametogenesis period (9 d).…”
Section: Materials Culture Of S Japonicaand Expression Analysis Of Sj...mentioning
confidence: 99%